(untitled) (Revista de Ensino em Artes, Moda e Design, 2022)
This paper shows a discussion on the learning experiences that design students acquire by relating their academic practice with the urban context through a creative exercise at Parque Chamizal, Ciudad Juárez, Chihuahua, México that complements activities in classroom. The participation of undergraduate students in Architecture and Master’s in Studies and Creative Processes in Art and Design within a multidisciplinary process promoted the realization of social skills for teamwork and dialogue. This allowed them to become aware of their reality and configure new places of experience, and decide, spaces full of meanings at a geographical, social and historical level with different possibilities for transformation.